.The role of community institutions in enhancing the intellectual security of Saudi youth - Al Shehri, Abdullah Hadi (Journal of Humanities & Social Sciences, 2019)
The main objective of this study is to identify the role of community institutions in enhancing the intellectual security of Saudi youth. This study is one of the descriptive analytical studies, which focused on describing and analyzing the contribution of societal institutions to the achievement of intellectual security among Saudi youth in an attempt to identify the main threats to intellectual security and to clarify the role of community institutions in addressing them; and formulating specific proposals that can enhance intellectual security in Based on activating the role of community institutions in order to fulfill their mandated tasks in this regard. The results of the study on the threats of intellectual security among the Saudi youth, that intellectual deviation is the most dangerous threat to intellectual security at the moment. The study pointed out that there are specific roles for the family, educational institutions, mosques and the media, and various media as community institutions in achieving intellectual security among young people in Saudi society. The study concluded by identifying some means of activating the role of community institutions in Saudi society in enhancing intellectual security among young people.